Enhanced muscle shortening and impaired Ca2+ channel function in an acute septic myopathy model - Friedrich, Oliver; Hund, Ernst; Wegner, Frederic von (Journal of neurology, 2010)
Myopathies in critically ill patients are increasingly documented. Various animal models of chronic sepsis have been employed to investigate reduced membrane excitability or altered isometric contractility of skeletal muscle. In contrast, immediate changes occurring during acute sepsis are significantly under-characterised; L-type Ca2+ channel function or isotonic shortening are examples. We recorded slowly activating L-type Ca2+ currents (ICa) in voltage-clamped single intact mouse skeletal muscle fibres and tested the effects of acute challenge with serum fractions from critical illness myopathy patients (CIM). Using a high-speed camera system, we simultaneously recorded unloaded fibre shortening during isotonic contractions with unprecedented temporal resolution (~1,600 frames/s). Time courses of fibre lengths and shortening velocity were determined from automated imaging algorithms. CIM fractions acutely induced depression of ICa amplitudes with no shifts in ICa-V-relations. Voltage-dependent inactivation was unaltered and ICa activation and inactivation kinetics were prolonged compared to controls. Unexpectedly, maximum unloaded speed of shortening was slightly faster following CIM serum applications, suggesting a direct action of CIM serum on weak-binding-state cross-bridges. Our results are compatible with a model where CIM serum might acutely reduce a fraction of functional L-type Ca2+ channels and could account for reduced SR Ca2+ release and force production in CIM patients. Acute increase in isotonic shortening velocity might be an early diagnostic feature suitable for testing in clinical studies. The acute challenge model is also robust against atrophy or fibre type changes that ordinarily would have to be considered in chronic sepsis models.
Online veröffentlicht am 4. November 2009
Gesehen am 10.07.2023